BIVALVE COMMUNITY STRUCTURE IN THE INTERTIDAL ZONE OF PASUMPAHAN ISLAND PADANG CITY WEST SUMATERA PROVINCE - Zani, Rahma; Tanjung, Afrizal; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Bivalvia is a class of the Mollusca phylum. Bivalvia is also known as Pelecypoda and Lamellibrankhiata. Bivalvia occupies an area of the intertidal zone, one of which is in the intertidal zone of Pasumpahan Island. But information about bivalves in the area does not exist. To know/understand information about the density and distribution pattern of bivalves on Pasumpahan Island, this research was conducted in January 2022. The sampling area was in the intertidal zone of Pasumpahan Island. Sampling was carried out at three stations, each station was divided into three transects. Bivalve sampling was carried out using a 1 x 1mm sieve. The movement of bivalves to the gravel substrate is very fast to avoid splashing waves. Bivalves samples were then identified. The density of bivalves in the intertidal zone of Pasumpahan Island ranged from 1.78-3.56 Ind/m2. Station 2 has a higher density of bivalves, namely 3.56 Ind/m2, the calculation of bivalves in the intertidal zone of Pasumpahan Island obtained bivalves distribution pattern data in groups